THE CONNECTION BETWEEN THE TYPE AND COLOR OF THE SEEDS AND THE AGRONOMIC VALUABLE TRAITS OF F5 HYBRIDS OF G.BARBADENSE L. - S. A. Usmanov; Toshmatova M. Sh.; K.O. Khudarganov; M. M. Abdullaeva (Journal Park Publishing, 2025)
The research results showed that, we could conclude that the type and color of seeds do not significantly affect the main of agronomic valuable traits. There was a weak correlation between some traits. The type and color of the undercut can be used as a marker attribute in breeding.
Keywords: Uzbekistan, cotton, lines, a raw cotton weight of one boll, fiber output, fiber length, correlation.